Can market segmentation lead to green paradox? Evidence from China. (1st September 2022) - Lai, Aolin; Wang, Qunwei; Cui, Lianbiao
Abstract: China has announced its commitment to peak carbon emissions before 2030 and reach carbon neutrality by 2060. However, market segmentation may hinder these achievements because it creates carbon leakage among provinces. This study empirically examines the impact of market segmentation on the effectiveness of environmental regulations based on a dynamic spatial panel approach using data for 30 Chinese provinces from 2004 to 2018. Our results showed that pure environmental regulation can significantly curb carbon emissions; however, under the influence of market segmentation, carbon emissions reduced in the region are released into the neighboring provinces through the carbon leakage pathway, while the total carbon emissions raised, leading to the "green paradox". The study also showed that the "green paradox" effect of market segmentation is more pronounced for provinces with a higher share of secondary industries, suggesting industrial transfer as the primary pathway of carbon leakage between provinces in China. Therefore, to effectively avoid the green paradox phenomenon, it is necessary to continuously promote market unification, optimize the industrial structure, and establish a unified carbon reduction system. This study clarified the relationship between market segmentation and the green paradox, thereby providing insights for China to achieve its carbon emission reduction and carbon neutrality goals. Highlights: We explore the dynamic correlation between market segmentation and carbon emissions. Market segmentation may cause "green paradox". Carbon emissions are released in adjacent provinces through carbon leakage pathways. Industrial transfer is major pathway for carbon leakage between provinces in China.